Multimodality Treatment for Hepatocellular Carcinoma With Portal Vein Tumor Thrombus - Kang Wang; Wei Guo; Min Shan Chen; Yi Mao; Bei Sun; Jie Shi; Yaojun Zhang; Yan Meng; Ye Fa Yang; Wen- Ming Cong; Meng Wu; Wan Yee Lau; et al. (2016)
The optimal treatment for hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT) remains controversial. We aimed to investigate the best treatment for patients with HCC with PVTT. From January 2002 to January 2014, the data from all consecutive patients with HCC with PVTT who underwent surgical treatment (ST),TACE,TACE combined with sorafenib (TACE-Sor), or TACE combined with radiotherapy (TACE-RT) in the 4 largest tertiary hospitals in China were analyzed retrospectively. The patients were divided into 3 subtypes according to the extent of PVTT in the portal vein (type I-III). The primary endpoint was overall survival (OS). A total of 1580 patients with HCC with PVTT were included in the study. The median survival times (MST) for ST (n = 745) for type I, II, and III patients (95% CI) were 15.9 (13.3–18.5), 12.5 (10.7–14.3), and 6.0 (4.3–7.7) months, respectively. The corresponding figures for patients after TACE (n = 604) were 9.3 (5.6–12.9), 4.9 (4.1–5.7), and 4.0 (3.1–4.9), respectively; for patients after TACE-Sor (n = 113) 12.0 (6.6–17.4), 8.9 (6.7–11.1), and 7.0 (3.0–10.9), respectively; and for patients after TACE-RT (n = 118) 12.2 (0–24.7), 10.6 (6.8–14.5), and 8.9 (5.2–12.6), respectively. Comparison among the different treatments for the 3 subtypes of PVTT patients after propensity score (PS) matching showed the effectiveness of ST to be the best for type I and type II PVTT patients, and TACE-RT was most beneficial for type III patients. Treatment was an independent risk factor of OS. ST was the best treatment for type I and II PVTT patients with Child-Pugh A and selected B liver function. TACE-RT should be given to type III PVTT patients.